Integrated Smart Packaging of Modified Silica/Anthocyanin/Nanocellulose for Preservation and Monitoring - Yu Ren; Jing Guo; Zehao Zhong; Jinjin Chen; Peng Jin; Yonghua Zheng; Zhengguo Wu (Foods)
Smart packaging not only has a preservation effect on food, but can also monitor the change of food quality in real time to ensure food safety. In this study, hollow mesoporous silica loaded with cinnamaldehyde was used as the antimicrobial agent, anthocyanin as the color developer, and nanocellulose as the film matrix, to obtain smart packaging with excellent antimicrobial activity and pH-responsive color development (CBF). Modified silica has a good regulatory characteristic on the release of cinnamaldehyde, and the cumulative release rate of cinnamaldehyde in the NH2-HMSN@CA preservative reaches 72% after 7 days. Additionally, the film has good antibacterial properties, with inhibition rates of 82% and 92% against E. coli and S. aureus, respectively. In addition, the film has good mechanical properties and water vapor permeability. In terms of pH response, the film shows excellent color rendering and good stability. Therefore, the CBF films can be applied to preservation and real-time monitoring of fruits and vegetables, meat, and other food products, which has great potential for intelligent food packaging.